2011
DOI: 10.1097/brs.0b013e3181fb3a42
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Reduces Perioperative Blood Loss in Cervical Laminoplasty

Abstract: TXA significantly reduced perioperative blood loss, primarily through a reduction in postoperative blood loss, in cervical laminoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
92
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 25 publications
6
92
1
2
Order By: Relevance
“…Although it has been assessed in several studies, the efficacy and safety of TXA for perioperative blood loss reduction during spine surgery has not been clearly demonstrated. 3,[13][14][15] In this study, 2 doses of TXA significantly reduced perioperative blood loss, crystalloid and colloid administration, and blood transfusions in adult patients undergoing elective complex laminectomy. The overall incidence of blood transfusions in the TXA group was 15.3% compared with 43.5% in the control group.…”
Section: Discussionmentioning
confidence: 64%
“…Although it has been assessed in several studies, the efficacy and safety of TXA for perioperative blood loss reduction during spine surgery has not been clearly demonstrated. 3,[13][14][15] In this study, 2 doses of TXA significantly reduced perioperative blood loss, crystalloid and colloid administration, and blood transfusions in adult patients undergoing elective complex laminectomy. The overall incidence of blood transfusions in the TXA group was 15.3% compared with 43.5% in the control group.…”
Section: Discussionmentioning
confidence: 64%
“…The mechanism of action is During their randomized prospective study, they reported a reduction in blood loss in both intra-and postoperative time periods in adult patients who underwent cervical laminoplasty. 36 As a theoretical outcome of the initiation of TXA administration, our major concern was that the antifibrinolytic effect of this medication might lead to an increase in venous thromboembolic events. However, recent publications suggest that TXA does not result in an increase in thromboembolic events.…”
Section: Discussionmentioning
confidence: 99%
“…10 Initial data supporting its effectiveness were from retrospective case series or heterogeneous cohort studies. [9][10][11][12][13][14][15] Subsequently, various prospective clinical trials analysed the performance of TXA in adolescents [16][17][18] and adults [19][20][21][22][23][24] undergoing several types of surgery of varying complexity, with divergent results. The 15 first meta-analysis on TXA use in spine surgery, published in 2008, 25 did not offer a clearly favourable recommendation because of the poor methodological quality of the studies included.…”
mentioning
confidence: 99%
“…4 The same reasoning would apply to TXA use in cervical surgery. Elwatidy and colleagues 19 and Tsutsumimoto and colleagues 20 failed to demonstrate efficacy of TXA in cervical 30 procedures, which is not surprising considering that patients with intraoperative bleeding volumes of less than 100 mL were included. Our results show that the larger the number of levels fused and the longer the duration of surgery, the more effective was TXA administration, coinciding with the findings of Peters 35 and colleagues.…”
mentioning
confidence: 99%